2019
DOI: 10.1021/acs.orglett.9b02604
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Copper-Catalyzed Electrophilic Dearomative Azidation of β-Naphthols

Abstract: The first example of copper-catalyzed enantioselective dearomative azidation of β-naphthols using a readily available N 3 -transfer reagent is reported. A series of 2-hydroxy-1-naphthamides bearing a complex N-substituent were converted to the corresponding products in high yields with up to 96% ee, and chiral 1-azido-2-hydroxy-1-naphthoates were obtained with up to 90% ee under mild reaction conditions. The azides could be further transformed into the corresponding 1,2,3-triazoles smoothly via "click" reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 65 publications
0
14
0
1
Order By: Relevance
“…By using a Cu‐catalyst modified with chiral N,N‐ligand 84 , Deng and co‐workers have shown that highly enantioselective dearomatizing azidation reactions are possible (Scheme 27). [57] In this method, hypervalent iodine‐based azide transfer reagent 83 is used and the method requires a carbonyl substituent at C2 of the naphthol. This facilitates two‐point binding of the substrate to the Cu‐center in advance of enolate‐like attack onto the azide electrophile.…”
Section: Discussionmentioning
confidence: 99%
“…By using a Cu‐catalyst modified with chiral N,N‐ligand 84 , Deng and co‐workers have shown that highly enantioselective dearomatizing azidation reactions are possible (Scheme 27). [57] In this method, hypervalent iodine‐based azide transfer reagent 83 is used and the method requires a carbonyl substituent at C2 of the naphthol. This facilitates two‐point binding of the substrate to the Cu‐center in advance of enolate‐like attack onto the azide electrophile.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the Sarkar group developed a similar reaction using the reagent system of NaN 3 /phenyl trimethylammonium tribromide (PTAB) under metal-free conditions . An enantioselective version of this transformation using hypervalent iodo azide reagent as azide source was achieved by the Deng group . Remarkably, employing Cu­(CH 3 CN) 4 ·PF 6 and a 4,6-dibenzofurandiyl-2,2′-bisoxazolin (dbfox) ligand resulted in the desired enantioenriched α-azido β-naphthalenones in excellent yields with moderate to high enantioselectivities (Scheme ).…”
Section: Azidation Of C–c Multiple Bondsmentioning
confidence: 99%
“…For example, it has been shown that chiral iron or copper catalysts can promote highly enantioselective electrophilic azide transfers. [ 27 , 66 ] In these processes, the electrophilic aminating agent is an azide‐containing hypervalent iodine(III) species. These species are often highly unstable; however, it has been shown that safer variants can be developed.…”
Section: α‐Amination Of Carbonyl Compoundsmentioning
confidence: 99%